2019
DOI: 10.21203/rs.2.12247/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UPLC-MS based urine untargeted metabolomic analyses to differentiate bladder cancer from renal cell carcinoma

Abstract: Purpose To discover biomarker panels that could distinguish cancers(BC & RCC) from healthy controls(HCs) and bladder cancers(BC) from renal cell carcinoma(RCC), regardless of whether with hematuria. Methods Totallys, 403 participants were enrolled in our study, with 146 BC patients(77 without hematuria and 69 with hematuria), 115 RCC patients (94 without hematuria and 21 with hematuria) and 142 gender- and age- matched HCs. Their midstream urine samples were collected and analysed by performing UPLC-MS.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…It has been frequently emphasized that carbohydrates are the most important metabolites that distinguish cancerous cells from healthy cells. 3538 In the present study, turanose metabolite differed in OC patients from BT patients ( p = ​​06.58E-04). In a study conducted by Cheng et al ., 12 a group of metabolite markers consisting of maltose, maltotriose, raffinose, and mannitol were determined to differentiate OC from BT with an AUC value of 0.832.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…It has been frequently emphasized that carbohydrates are the most important metabolites that distinguish cancerous cells from healthy cells. 3538 In the present study, turanose metabolite differed in OC patients from BT patients ( p = ​​06.58E-04). In a study conducted by Cheng et al ., 12 a group of metabolite markers consisting of maltose, maltotriose, raffinose, and mannitol were determined to differentiate OC from BT with an AUC value of 0.832.…”
Section: Discussionmentioning
confidence: 40%
“…In a previous study, five biomarkers, including L-tyrosine, were found to be important in the urine samples of bladder cancer group (AUC:0.913). 36 L-tyrosine amino acid was defined as a biomarker showing a significant difference between prostate cancer and HC (p < 0.0001). 39 17 metabolites, including L-tyrosine, were identified as potential biomarkers to differentiate patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%